THE BINDING POWER OF ELECTRONIC SIGNATURES IN CIVIL AGREEMENTS: A COMPARATIVE STUDY OF THE CIVIL CODE AND ELECTRONIC INFORMATION AND TRANSACTIONS LAW - Dahlan, Dahlan; Bangun, Anza Ronaza; Prakarsa, Taruna (PRANATA HUKUM, 2025)
Advances in information technology have brought significant changes in the way people draft and agree to agreements, including through the use of electronic signatures. In the legal context in Indonesia, the existence of electronic signatures has been given legitimacy through the Electronic Information and Transactions Law (UU ITE). However, on the other hand, the conventional civil law system is still based on traditional principles regulated in the Civil Code (KUHPerdata). This study aims to examine the extent of the binding force of electronic signatures in the realm of civil agreements, while at the same time comparing the approach of the Civil Code and the provisions of the ITE Law. The research was conducted using a normative legal method, through a review of laws and comparative legal analysis. The results of the study show that although normatively the ITE Law has provided a legal standing for electronic signatures, the Civil Code has not fully adapted to the dynamics of digital law. This inequality can raise doubts in practice, especially in terms of proof and validity of contracts. For this reason, steps are needed to harmonize classical civil regulations and digital laws and regulations in order to provide legal certainty for the parties in agreements made electronically.